The temporal evolution of HCHO and changes in atmospheric composition in the southeast of the United Kingdom - Balendra V.S. Chauhan; Kirsty L. Smallbone; Maureen Berg; Kevin P. Wyche (Case Studies in Chemical and Environmental Engineering)
Formaldehyde (HCHO) is a significant atmospheric pollutant with adverse effects on human and environmental health. This case study investigates seasonal variations in HCHO concentrations and their relationship with tropospheric ozone (O3) levels in the Southeast of the United Kingdom. Using hourly data collected from June 2015 to May 2023 at the Brighton Atmospheric Observatory, the research analyzes the interplay between atmospheric chemistry, meteorological parameters, and pollutant transport dynamics. Results reveal pronounced peaks in HCHO concentrations during summer months, reaching up to 9.5–10 μg/m³ around 12:00. This surge is attributed to heightened photochemical activity driven by increased solar radiation and temperatures. Regression analyses demonstrate a strong positive correlation (97 %) between summertime HCHO concentrations and air temperature. Elevated temperatures accelerate VOC oxidation reactions, leading to increased HCHO formation. The study also finds a significant correlation (81 %) between summertime tropospheric O3 and air temperature. This suggests that higher temperatures enhance photochemical reactions involving O3 precursors, contributing to elevated O3 levels. Wind pattern analysis reveals the dominance of southwesterly winds in transporting HCHO throughout the year, with concentrations peaking at wind speeds of 15–20 m/s. During summer, northeastern and easterly winds become more influential in carrying tropospheric O3, highlighting seasonal shifts in transport pathways. These findings provide valuable insights into air quality dynamics and underscore the importance of targeted interventions for sustainable air quality management. Understanding the factors influencing HCHO and O3 concentrations is crucial for developing effective mitigation strategies to protect human and environmental health.